2003
DOI: 10.1177/00222194030360010601
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Functioning as Measured by the WISC-R

Abstract: Patterns of performance on the Wechsler Intelligence Scale for Children-Revised (WISC-R) have been proposed as useful tools for the identification of children with learning disabilities (LD). However, most of the studies of WISC-R patterns in children with LD have been plagued by the lack of a typically achieving comparison group, by failure to measure individual patterns, and by the lack of a precise definition of LD. In an attempt to address these flaws and to assess the presence of patterns of performance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 48 publications
(56 reference statements)
5
18
1
Order By: Relevance
“…In our study, the verbal IQ in the probands was lower than that of performance IQ, which support the hypothesis that verbal IQ is correlated more strongly with the reading ability than the performance IQ (Bishop & Butterworth, 1980). The conclusion from the studies is that verbal and performance IQ may show discrepancy pattern in children with learning disorder or controls (D'Angiulli & Siegel, 2003) Hence, IQ cannot be considered as a proxy for learning potential (Francis, Fletcher, Shaywitz, Shaywitz, & Rourke, 1996) and…”
Section: Discussionsupporting
confidence: 78%
“…In our study, the verbal IQ in the probands was lower than that of performance IQ, which support the hypothesis that verbal IQ is correlated more strongly with the reading ability than the performance IQ (Bishop & Butterworth, 1980). The conclusion from the studies is that verbal and performance IQ may show discrepancy pattern in children with learning disorder or controls (D'Angiulli & Siegel, 2003) Hence, IQ cannot be considered as a proxy for learning potential (Francis, Fletcher, Shaywitz, Shaywitz, & Rourke, 1996) and…”
Section: Discussionsupporting
confidence: 78%
“…Another useful finding is that the performance IQ scores for all participants in this study tended to be approximately 10 points higher than verbal IQ, a pattern typically seen in reading-disabled subtypes (D'Angiulli & Siegel, 2003). A study exploring these subtypes identified a subgroup with a VIQ= PIQ difference of 4.5 points, which has often been associated with behavioral interference (Williams et al, 1992)-a finding relevant to this sample.…”
Section: Using Multisensory Phonicssupporting
confidence: 51%
“…The WISC-III was used to determine participants' intellectual functioning and to evaluate whether verbal and performance scores correlated with gains in reading scores, as noted by previous researchers (Bow, 1988;D'Angiulli & Siegel, 2003;Rourke & Fuerst, 1992;Simpson et al, 1992;Williams, Gridley, & Fitzhugh-Bell, 1992). Reliability and validity evidence for WISC-III scores is found in the test manual.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent studies found support for Bannatyne's classification system on WISC and WISC-R (Clarizio & Bernard, 1981;Rugel, 1974;M. D. Smith, Coleman, Dokecki, & Davis, 1977), whereas others demonstrated its limited diagnostic validity (D'Angiulli & Siegel, 2003;Henry & Wittman, 1981;Kavale & Forness, 1984;McKay, Neale, & Thompson, 1985;Vance & Singer, 1979). Kaufman (1981) stated that although some studies reported statistically significant mean differences in the composite scores between LD and controls, the proportions of individuals in the LD group displaying the Bannatyne pattern are quite small and their contribution to differential diagnosis is limited.…”
Section: Introductionmentioning
confidence: 99%